Knot bad amigurumi learn crochet stitches and techniques to create cute creatures with 25 easy patterns - Green-Hite, Vincent (Quarry Books, 2022)
"Knot Bad Amigurumi features easy and fun techniques for creating unique and adorable crochet characters-including a turtle, bee, rocket ship, and boba tea, along with ideas for personalizing creations"--
Includes index. - Description based on print version record and CIP data provided by publisher; resource not viewed
Keywords: Amigurumi -- Patterns; Crocheting -- Patterns; Soft toy making; Travaux au crochet; Modèles; Jouets de tissu; Fabrication; Amigurumi; Crocheting; Patterns